2024
DOI: 10.1039/d3qi02043f
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen defect engineering on low-crystalline iron(iii) oxyhydroxide as a highly efficient electrocatalyst for water oxidation

Yaning Fan,
Junjun Zhang,
Kongliang Luo
et al.

Abstract: The defects optimized the adsorption capacity of the reaction intermediates during the catalytic process and finally improved the catalytic efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…50 The above results suggested the formation of Ni-O-Ni (Co-O-Co) and NiOOH (CoOOH) on the surface of the catalyst aer OER process. 51,52 The above analysis results veried the structural shrinkage of the MOFs, accompanied with the destruction of the organic ligand BTC during water oxidation. This resulted in the presence of the interconnected NiO/CoO and NiOOH/CoOOH acting as the more active phase.…”
Section: Resultsmentioning
confidence: 92%
“…50 The above results suggested the formation of Ni-O-Ni (Co-O-Co) and NiOOH (CoOOH) on the surface of the catalyst aer OER process. 51,52 The above analysis results veried the structural shrinkage of the MOFs, accompanied with the destruction of the organic ligand BTC during water oxidation. This resulted in the presence of the interconnected NiO/CoO and NiOOH/CoOOH acting as the more active phase.…”
Section: Resultsmentioning
confidence: 92%
“…49 Furthermore, the phase angle of the Bode phase plots for each electrode noticeably decreases with increasing potential, indicating a reduction in faradaic resistance and thereby facilitating electron transfer during intermediate adsorption. 17,50–53…”
Section: Resultsmentioning
confidence: 99%
“…12 In recent years, various compounds such as phosphides, borides, nitrides, hydroxides, selenides and sulfides have been widely reported for the alkaline electrolyte OER and bifunctional water electrolysis. 13–19 However, recent studies have shown that these compounds exhibit instability at a high anodic potential required for the OER process. They undergo phase transformation to form the corresponding metal (oxy)hydroxides, which should be considered as a truly active component of the OER process.…”
Section: Introductionmentioning
confidence: 99%
“…This should open the way to cross-validation between theory and experiment, which should lead to a deeper understanding and then, eventually, to the rational design of much-needed more efficient and sustainable optimized catalysts in both oxidation and OER catalysis. In perspective, it will also be very interesting to further extend our approach by including defects such as oxygen vacancies in the surface energetics [53] or more complex composite architectures [54,55].…”
Section: Discussionmentioning
confidence: 99%